Localised surface plasmon mediated energy transfer in quantum dot systems - Zhang, Xia (Trinity College (Dublin, Ireland). School of Physics, 2015)
Nonradiative energy transfer to metal nanoparticles (NPs) is a technique used for optical- based distance measurements which is often implemented in sensing. Both Forster resonant energy transfer (FRET) and nanometal surface energy transfer (NSET) mechanisms have been proposed for emission quenching in proximity to metal NPs. Here quenching of emission of colloidal quantum dots (QD) in proximity to a monolayer of gold NPs is investigated. Five differently sized CdTe QDs are used to probe the wavelength dependence of the quenching mechanism as their emission peak moves from on resonance to off resonance with respect to the localized surface plasmon (LSP) peak of the Au NP layer.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin